Highlighting real capacitor behavior in liquid ammonia of passivated n-InP by thin Polyphosphazene film - Gianluca Visagli; Arnaud Etcheberry; Anne-Marie Gonçalves (Electrochemistry Communications)
Semiconductor/liquid junctions exhibit distinctive electrochemical behaviors. This study investigates the passivation of lightly doped (1015 cm−3) n-type indium phosphide (n-InP) in liquid ammonia. Under photoanodic conditions, a Polyphosphazene (PPP) film forms on the InP surface. The formation of PPP ultra-thin film was confirmed through X-ray photoelectron spectroscopy. Cyclic voltammetry revealed a progressive positive shift in the onset potential for photocurrent, indicating successful progressive passivation. Capacitance–voltage measurements showed a constant capacitance (≈ 1.3 μF.cm−2) over 400 mV after passivation, signifying the formation of a stable capacitor-like structure at the interface in a large potential domain. Cyclic voltammograms acquired at different scan rates demonstrated that the current was proportional to the scan rate, confirming the capacitive nature of the InP/PPP interface. The same interface capacitance was also quantified from the slope of the linear fit between the current and scan rate, showing that the PPP film acts as a dielectric layer with a fixed capacitance. This capacitor-like behavior leads the semiconductor in accumulation configuration from open circuit potential to lower potentials. To balance the electrical charges, the PPP should be positively charged in this range of potentials. The capacitance was used to determine the relative dielectric constant of the PPP film, which was found to be approximately 6.9. This value is consistent with that of polymeric materials exhibiting good insulating properties, further supporting the effective dielectric behavior of the PPP layer. This capacitor-like behavior alters the electrochemical response and stability of the InP/NH₃ Liq. interface, underscoring its potential for innovative electrochemical applications.